ANALISIS KINERJA LALU LINTAS PADA RUAS JALAN BACHARUDDIN JUSUF HABIBIE DENGAN MENGGUNAKAN PERANGKAT LUNAK VISSIM - Nur Fauziah Juliana Hunta; Yuliyanti Kadir; Frice Lahmudin Desei (Composite Journal, 2025)
The Bacharuddin Jusuf Habibie Road, which underwent improvements compared to the previous year, has not yet experienced traffic congestion. However, with increasing vehicles, congestion will likely occur in the coming years. Objective: To analyze the road characteristics, including geometric features, speed, travel time, traffic volume, and composition; road performance, free-flow speed, density, road capacity, degree of saturation, and level of service; and simulation results using VISSIM software. Methodology: The study utilized both primary and secondary data. Primary data were collected through field observations, while secondary data were sourced from journals, books, and government agencies. Results: The analysis shows the highest traffic volume occurs on Tuesdays between 16:00-17:00, with a total volume of 2,710 vehicles/hour or 1,117.8 passenger car units (PCU)/hour, predominantly consisting of motorcycles (82.32%), followed by sedans (11.77%), passenger vehicles (0.01%), pickup trucks (4.78%), small and large buses (0.19%), two-axle trucks with 4 and 6 wheels (0.92%), and articulated trucks (0.01%). Conclusion: The performance analysis of the Bacharuddin Jusuf Habibie Road in Bone Bolango Regency, utilizing the PKJI (Indonesian Highway Capacity Manual) 2023 method, reveals a free-flow speed of 46.269 km/h, a traffic density of 2.08 vehicles/hour/m, a road capacity of 1,484 PCU/hour, degree of saturation of “0.38” indicates a stable flow with very good condition and is categorized as A. Then, the level of service D is observable from vehicles speed according to the Government Regulations of 2015